Trends in active commuting to school among Czech schoolchildren from 2006 to 2014 - Pavelka, Jan; Sigmundová, Dagmar; Hamřík, Zdeněk; Kalman, Michal; Sigmund, Erik; Mathisen, Frida (Central European Journal of Public Health, 2017)
OBJECTIVE: Active commuting (AC) is an important factor in increasing the total daily physical activity (PA) in children, which is significant for their health and positive physical behaviour in adulthood. The objective of the study was to describe trends in active commuting to school among Czech girls and boys aged 11-15 years from 2006 to 2014, using data from the Health Behaviour in School-aged Children (HBSC) study. METHODS: To investigate trends in AC among Czech children of school age data obtained from the HBSC surveys carried out in 2006, 2010, and 2014 was used. The study sample comprised 12,273 respondents, out of whom 5,992 (48.8%) were boys and 6,281 (51.2%) girls. The overall trends in AC were evaluated using logistic regression analysis. RESULTS: Compared with 2006, there was an overall decrease in AC among the 13-year-old boys and 13-year-old girls (boys - 1.8% in 2006 to 50.1% in 2014, girls - 69.3% in 2006 to 46.3% in 2014). The proportion of children AC (walking and cycling) to school significantly decreased from 74.3% in 2006 to 53.4% in 2014. CONCLUSION: This study demonstrated that AC to school decreased sharply among Czech children of school age from 2006 to 2014. However, walking was the most frequently used mode of travel. The boys were significantly more likely to cycle to school compared to the girls. PA interventions for youth should encourage participation in AC to school in the Czech Republic.
Keywords: zdravotnické přehledy; Female; dítě; ženské pohlaví; průřezové studie; longitudinální studie; Adolescent; Transportation; lidé; školy; Schools; Humans; zdravé chování; Cross-Sectional Studies; cyklistika; doprava; Male; Czech Republic; Walking; Česká republika; Child; Health Surveys; mužské pohlaví; mladiství; chůze; Longitudinal Studies; Bicycling; Health Behavior